The Importance of Entry to Canadian Manufacuring, with an Appendix on Measurement Issues - Baldwin, John R.. (OECD Science, Technology and Industry Working Papers, 2002)
Understanding the importance of the dynamic entry process in the Canadian economy involves measuring size of entry. The main purpose of this paper is to summarise the information that we have on the amount of entry in Canada. The paper also fulfils another purpose. Some studies have focused on cross-country comparisons (Geroski and Schwalbach, 1991: OECD, 2001). Interpretation of the results of these studies is difficult unless methodological issues regarding how entry is measured are addressed. Without an understanding of the extent to which different databases produce different results, international comparisons are difficult to evaluate. Cross-country comparisons that are derived from extremely different data sources may be misleading because of the lack of comparability. Since there is more than one reliable database that can be used to estimate entry in Canada, this paper asks how measured entry rates vary across different Canadian databases. By examining the difference in entry ...